Effect of air-preheating on NOx emissions from a gas turbine combustor - Mustafa, Azeman (Faculty of Chemical & Natural Resources Engineering, 1994)
A 76 mm diameter can combustor equipped with a 45° curved-blade radial swirler was used to study the effect of high inlet temperature gas turbine combustion on NOx emission characteristics. High inlet temperature combustion was simulated using preheat air at 400°K, 600°K, 740°K and 900°K. Natural gas was investigated using passage injection technique. It was demonstrated that increasing the inlet air temperature significantly widened the weak extinction limit and improved the NOx emission characteristics. An optimum NOx emission of less than 4.5 ppm at 15% oxygen, compatible with 99% efficiency was demonstrated at 900K inlet temperature. It was also demonstrated that with high inlet temperature operation lean well-mixed combustion required for an adequate control of NOx emissions could be achieved. The major conclusion reached is that high inlet temperature combustion could be a promising approach for low NOx emissions with high combustion efficiency and good flame stability.